Changes in immunological profile as a function of urbanization and lifestyle. Issue 4 (December 2014) - Mbow, Moustapha; de Jong, Sanne E.; Meurs, Lynn; Mboup, Souleymane; Dieye, Tandakha Ndiaye; Polman, Katja; Yazdanbakhsh, Maria
Summary Differences in lifestyle and break with natural environment appear to be associated with changes in the immune system resulting in various adverse health effects. Although genetics can have a major impact on the immune system and disease susceptibility, the contribution of environmental factors is thought to be substantial. Here, we investigated the immunological profile of healthy volunteers living in a rural and an urban area of a developing African country (Senegal), and in a European country (the Netherlands). Using flow cytometry, we investigated T helper type 1 (Th1), Th2, Th17, Th22 and regulatory T cells, as well as CD4+ T‐cell and B‐cell activation markers, and subsets of memory T and B cells in the peripheral blood. Rural Senegalese had significantly higher frequencies of Th1, Th2 and Th22 cells, memory CD4+ T and B cells, as well as activated CD4+ T and B cells compared with urban Senegalese and urban Dutch people. Within the Senegalese population, rural paritcipants displayed significantly higher frequencies of Th2 and Th22 cells, as well as higher pro‐inflammatory and T‐cell activation and memory profiles compared with the urban population. The greater magnitude of immune activation and the enlarged memory pool, together with Th2 polarization, seen in rural participants from Africa, followed by urban Africans and Europeans suggest that environmental changes may define immunological footprints, which could have consequences for disease patterns in general and vaccine responses in particular.